2021
DOI: 10.1177/15280837211022614
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different parameters in tribological characteristics of pineapple/sisal/TiO2 filler incorporation

Abstract: In this experimentation hybrid composites using natural fibers and titanium oxide (TiO2) nano filler were fabricated using compression moulding technique. Pineapple (P) and Sisal (S) fibers were used as the natural reinforcements with epoxy as the matrix material. The mechanical results of flexural, impact and tensile properties found good improvement in the properties with SP fiber reinforcement (1:1 ratio) and TiO2 filler addition. The combination with 40 wt.% SP/5 wt.% TiO2 observed better mechanical result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Polyurethane films are widely used in coatings, adhesives, biomedicine, the textile industry, and the paper industry due to their excellent elasticity and abrasion resistance 24–26 . Nowadays, epoxy resin as a matrix is widely used in carbon fibers, glass fibers, and various natural fibers 27–29 . Therefore, it is of great significance to improve the bonding performance between polyurethane sizing agent and epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane films are widely used in coatings, adhesives, biomedicine, the textile industry, and the paper industry due to their excellent elasticity and abrasion resistance 24–26 . Nowadays, epoxy resin as a matrix is widely used in carbon fibers, glass fibers, and various natural fibers 27–29 . Therefore, it is of great significance to improve the bonding performance between polyurethane sizing agent and epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was proven that the incorporation of titanium oxide nanofiber into a metal matrix (aluminum) could improve the metal matrix mechanical properties [ 26 , 27 , 28 ]. In addition, many researchers used titanium oxide as a filler for enhancing the tribological properties of materials used in biomedical applications [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The filler substitutes fill in the gaps between the fiber and matrix phases, improving the characteristics. The use of TOPSIS for multiresponse optimization revealed that hybrid SP had the most impact on the overall tribological properties of natural fiber composites, with rank 1 being the most important, followed by filler incorporation [11]. Filler mixing improves fiber/matrix adhesion and increases mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%